2019
DOI: 10.2478/jeb-2019-0015
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Mandatory Pension Funds: Case of Croatia

Abstract: The aim of this paper is to examine performance of pension funds in Croatia, or more precisely, to measure the technical efficiency of mandatory pension funds. The main role of the pension funds is to collect and invest the money contributed by the employer or the employee during working years until retirement. Therefore, development of pension funds as institutional investors is especially important for capital markets as well as for the whole economy. By applying the methodology of data envelopment analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…The calculations made allowed us to draw the conclusion about the phenomenon of very weak, though statistically significant, performance repeatability achieved by open pension funds operating on the Polish market. The analysis of empirical data also confirms previous local and international results (Bohl, Lischewski, & Voronkova, 2011;Draženović, Hodžić, & Maradin, 2019;Kurach, 2019) indicating that the rates of return recorded by individual entities become increasingly similar over time. The study highlighted the clear advantages of the methods adopted to study distribution dynamicsabove all, the ease of interpretation of the results obtained.…”
Section: Discussionsupporting
confidence: 83%
“…The calculations made allowed us to draw the conclusion about the phenomenon of very weak, though statistically significant, performance repeatability achieved by open pension funds operating on the Polish market. The analysis of empirical data also confirms previous local and international results (Bohl, Lischewski, & Voronkova, 2011;Draženović, Hodžić, & Maradin, 2019;Kurach, 2019) indicating that the rates of return recorded by individual entities become increasingly similar over time. The study highlighted the clear advantages of the methods adopted to study distribution dynamicsabove all, the ease of interpretation of the results obtained.…”
Section: Discussionsupporting
confidence: 83%
“…Pension funds included in dataset have been categorised into four groups: equity (6), mixed (5), bond (6) and index (6) funds. Sample size is comparable with that of other studies from the CEE region or Balkan region (Draženović et al, 2019;Kabašinskas et al, 2017;Kurach, 2019;Matek et al, 2015;Mešťan et al, 2016).…”
Section: Sample and Data Preparationsupporting
confidence: 84%
“…Better performance of four mandatory pension funds compared to that of benchmark has been initially confirmed also in Croatia (Matek et al, 2015), although recent studies have shown rather weak performance of these pension funds (Draženović et al, 2019). Draženović et al (2019) has proved that, between 2015 and 2018, only 5 out of 12 compulsory pension funds have achieved comparable or better returns than benchmark. Furthermore, another study has proved, that for 10 out of 12 analysed pension funds in Poland, their portfolio managers have been unable to adjust managed portfolio to take advantage of market trends, thereby underperforming during period from February 2014 to December 2016 (Kurach, 2019).…”
Section: Literature Reviewmentioning
confidence: 86%
See 2 more Smart Citations